The Effect of the Implementation the Wordwall Application on the Mastery German Vocabulary for the 11th Graders of SMAN 7 Malang - Zahra Rahma Zunairoh; Sawitri Retnantiti (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
This study aims to determine the effect of the implementation the Wordwall application on the mastery German vocabulary for the 11th graders of  SMAN 7 Malang. The approach used in this research is quantitative with quasi-experimental method andresearch design pretest and posttest control group. method Purposive sampling used in sampling is a class XI student Interests German Cross, XI IPS 2 as the control class (using PowerPoint) and XI Languages 1 as an experimental class (using the application Wordwall).The test method was used as a data collection technique. Furthermore, the data obtained were analyzed by prerequisite tests and hypothesis testing. Test the hypothesis using the T test. The results of the analysis show that the probability value (p) less than tcount  = 2.001717 less than 4.247526, which means H0 is rejected. Thus, it can be concluded that there is an effect of the implementation the Wordwall application on the mastery German vocabulary for the 11th graders of  SMAN 7 Malang.